A metallic 3D printed K‐band quasi‐pyramidal‐horn antenna array. Issue 7 (5th March 2020) - Wang, Zhaoyan; Zhang, Bing; Huang, Kama
Abstract: A K ‐band (18‐27 GHz) antenna array is presented in this article. By deposing the quasi‐pyramidal‐horn upon a print circuit board (PCB), a traveling‐wave quasi‐pyramidal‐horn antenna is formed. Parasitic rings are introduced to decrease the quality factor for an extended bandwidth. The antenna element demonstrates impedance bandwidth 18.6 to 23.3 GHz. The gain is 10.3 dBi at 20.4 GHz with a stable radiation pattern. The impedance bandwidth of a 2 × 2 array is 18.3 to 22.7 GHz, with a maximum gain of 15.2 dBi at 20.4 GHz. The simulated and measured radiation patterns on E ‐ and H ‐planes at 20.4 GHz agree well. Taking advantage of the 3D printing technology, the quasi‐pyramidal horn is fabricated by selective laser melting using aluminum alloy for time‐saving and process simplicity. The proposed design highlights the hybrid usage of PCB and metallic 3D printing technology in fabricating microwave devices. It is a capable candidate for wireless communication.